2010
DOI: 10.1111/j.1751-9004.2010.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Novelty Categorization Theory

Abstract: Novelty Categorization Theory (NCT) attempts to predict when people perceive events as novel and how they process novel events across different domains. It is predicted that broad mental categories reduce the perception of an event being novel via inclusion processes, whereas narrow categories increase it via exclusion processes. Furthermore, based on a ‘motive to know’, when preparing for novel events, people broaden both perception and mental categories, because to understand novel information, it is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 114 publications
(194 reference statements)
4
48
1
Order By: Relevance
“…For example, the jeans shopper with a local processing style may buy the jeans because of its soft texture by overlooking its miserable fit. Furthermore, because novelty naturally involves a funnel sequence from novel to familiar (Förster et al, ), it would be important to examine changes in perception over time. Would dating partners, for example, listen to the global meaning of a communication by missing important details, but then after some time when a relationship develops, would they focus more and more on specifics (Förster, Özelsel, & Epstude, )?…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, the jeans shopper with a local processing style may buy the jeans because of its soft texture by overlooking its miserable fit. Furthermore, because novelty naturally involves a funnel sequence from novel to familiar (Förster et al, ), it would be important to examine changes in perception over time. Would dating partners, for example, listen to the global meaning of a communication by missing important details, but then after some time when a relationship develops, would they focus more and more on specifics (Förster, Özelsel, & Epstude, )?…”
Section: Discussionmentioning
confidence: 99%
“…For example, the farther away in the future an event will take place, the more psychologically distant this event will be. Others suggested that distant events will create a feeling of novelty (Förster et al, ). Construal Level Theory (CLT; Liberman & Trope, ; Liberman et al, ; Trope & Liberman, ) further suggests that more psychologically distal stimuli are represented on a higher level, in a more abstract, super‐ordinate and general way.…”
Section: Construal Level Theorymentioning
confidence: 99%
See 3 more Smart Citations